Judicial Independence in the EU – A Puzzle - Jerg Gutmann; Stefan Voigt (University of Hamburg, Institute of Law and Economics (ILE), 2017)
Based on data from the EU Justice Scoreboard, we identify a puzzle: National levels of judicial independence (as perceived by the citizens of EU member states) are negatively associated with the presence of formal legislation usually considered as conducive to judicial independence. We try to resolve this puzzle based on political economy explanations and specificities of legal systems, but to no avail. We then ask whether cultural traits can help to put together the puzzle. And indeed, countries with high levels of generalized trust (and to a lesser extent individualistic countries) exhibit increased levels of de facto judicial independence and, at the same time, reduced levels of de jure judicial independence. The combination of these two effects can explain why judicial reforms that should be conducive to an independent judiciary may seem to have adverse consequences. We conclude that cultural traits are of fundamental importance for the quality of formal institutions, even in societies as highly developed as the EU member states.
Keywords: H11; K40; O40; P51; 330; judicial independence; EU Justice Scoreboard; informal institutions; culture